2011
DOI: 10.1590/s1807-59322011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Detection of deletions at 7q11.23 in Williams-Beuren syndrome by polymorphic markers

Abstract: INTRODUCTION:Williams-Beuren syndrome (WBS; OMIM 194050) is caused by a hemizygous contiguous gene microdeletion at 7q11.23. Supravalvular aortic stenosis, mental retardation, overfriendliness, and ocular and renal abnormalities comprise typical symptoms in WBS. Although fluorescence in situ hybridization is widely used for diagnostic confirmation, microsatellite DNA markers are considered highly informative and easily manageable.OBJECTIVES:This study aimed to test the microsatellite markers for the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
1
18
0
3
Order By: Relevance
“…A strong maternal bias exists for the NF1 deletion, but studies were small in size. 27,28 For Williams Beuren syndrome (WBS [MIM 194050]), which results from NAHR events between flanking LCRs, or SDs, in chromosomal region 7q11.23, we performed a meta-analysis on existing data [29][30][31][32][33] and found no gender bias of origin for the 7q11.23 deletion among 471 probands: 248 (53%) were of maternal origin and 223 (47%) were of paternal origin (two-tailed p ¼ 0.27). There is, however, an important confounding feature for WBS in that the presence of an inversion polymorphism 32 greatly increases risk of meiotic NAHR events.…”
mentioning
confidence: 99%
“…A strong maternal bias exists for the NF1 deletion, but studies were small in size. 27,28 For Williams Beuren syndrome (WBS [MIM 194050]), which results from NAHR events between flanking LCRs, or SDs, in chromosomal region 7q11.23, we performed a meta-analysis on existing data [29][30][31][32][33] and found no gender bias of origin for the 7q11.23 deletion among 471 probands: 248 (53%) were of maternal origin and 223 (47%) were of paternal origin (two-tailed p ¼ 0.27). There is, however, an important confounding feature for WBS in that the presence of an inversion polymorphism 32 greatly increases risk of meiotic NAHR events.…”
mentioning
confidence: 99%
“…We curated studies that reported parental origin of CNV (deletions and duplications) at these loci using a systematic PubMed search and the following set of inclusion criteria: 1) the study detailed parent of origin data within one of the NAHR-mediated loci as designated by Coe et al, 2014 [8], (2) the study reported parent of origin data for non-imprinted loci, (3) data were reported for more than 10 families with affected children, and (4) the study clearly treated monozygotic twins as one meiosis event (Additional File 1: Supplemental Methods and Additional File 2: Table S1). We identi ed six loci for further analysis: 5q35.3 [31,32], 7q11.23 [24,[36][37][38][39][40][41][42], 16p11.2 [26], 17p11.2 [43][44][45], 17q11.2 [27][28][29], 22q11.2 [30,37,[46][47][48][49][50][51]. At a seventh locus (3q29) we generated new data to determine the parent of origin for de novo events.…”
Section: Parent Of Origin Determination Literature Search and Data Cumentioning
confidence: 99%
“…Médica (Gilbert-Dussardier et al, 1995;Dutly and Schinzel, 1996;Urban et al, 1996;Dutra et al, 2011). Com essa técnica é possível definir a origem parental do cromossomo que abriga a microdeleção e mapear os pontos de quebra cromossômica.…”
Section: Marcadores Polimórficos De Dnaunclassified